Dysfunctional Brain Dynamics of Parkinson's Disease and the Effect of Acute Deep Brain Stimulation - Li, Zhibao; Ren, Guoping; Liu, Chong; Wang, Qiao; Liang, Kun; Han, Chunlei; Qiao, Hui; Zhang, Jianguo; Wang, Qun; Meng, Fangang (Frontiers in Neuroscience, 2021)
Abstract Background: Parkinson’s disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease, and deep brain stimulation (DBS) can effectively alleviate PD symptoms. Although previous studies have detected network features of PD and DBS, few studies have considered their dynamic characteristics. Objective: We tested two hypotheses. (1) Reduced brain dynamics, as evidenced by slowed microstate dynamic change, is characteristic of PD and is related to the movement disorders of PD patients. (2) Therapeutic acute DBS can partially reverse slow brain dynamics in PD to healthy levels. Methods: We used electroencephalography microstate analysis based on high density (256-channel) electroencephalography to detect the effects of PD and DBS on brain dynamic changes on a sub-second timescale. We compared 21 healthy controls with 20 PD patients who were in either DBS-OFF or DBS-ON states. Assessment of movement disorder using the Unified Parkinson’s Disease Rating Scale III was correlated with microstate parameters. Results: Compared with healthy controls, PD patients displayed a longer mean microstate duration with less occurrence per second, which were significantly associated with movement disorder. In PD patients, some parameters of microstate analysis were restored towards healthy levels after DBS. Conclusions: Resting-state electroencephalography microstate analysis is an important tool for investigating brain dynamic changes in PD and DBS. PD can cause a slowing of brain dynamic change and therapeutic acute DBS can partially reverse this change towards a healthy level.